2014
DOI: 10.5888/pcd11.140059
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Contraceptive Use and Gestational Diabetes: Missouri Pregnancy Risk Assessment Monitoring System, 2007–2008

Abstract: IntroductionThe efficacy and safety of contraceptives have been questioned for decades; however, whether a relationship exists between hormonal contraceptives and gestational diabetes (GDM) is undetermined. The aim of this study was to investigate whether maternal risk for GDM was influenced by type of contraceptive method used before pregnancy.MethodsData collected in 2007 and 2008 by the Missouri Pregnancy Risk Assessment Monitoring System (PRAMS) were analyzed to determine if type of contraception before pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…In this current study, we observed previous use of oral contraceptive as independent risk factor of gestational diabetes. This is in consistent with a study by Kramer et al ( 21 ), who reported the use of oral contraceptives is associated with gestational diabetes ( 21 ). The agreement between the current and previous study provides evidence that hormonal contraceptive methods may increase a woman’s risk for GDM since most oral contraceptives are made up of oestrogen and progesterone which in excess induces hypercortisolism and therefore leading to insulin resistance and hyperglycaemia in pregnancy.…”
Section: Discussionsupporting
confidence: 93%
“…In this current study, we observed previous use of oral contraceptive as independent risk factor of gestational diabetes. This is in consistent with a study by Kramer et al ( 21 ), who reported the use of oral contraceptives is associated with gestational diabetes ( 21 ). The agreement between the current and previous study provides evidence that hormonal contraceptive methods may increase a woman’s risk for GDM since most oral contraceptives are made up of oestrogen and progesterone which in excess induces hypercortisolism and therefore leading to insulin resistance and hyperglycaemia in pregnancy.…”
Section: Discussionsupporting
confidence: 93%
“…This means that women who were nonusers were more likely to have risk factors for diabetes than users, and this is logical as risk factors are limitations or contraindications for oral contraceptive treatment. A positive association between oral contraceptives and gestational diabetes mellitus has already been reported 10 …”
Section: Discussionmentioning
confidence: 83%
“…In many populations, the incidence of type 2 diabetes is higher in men than in women, and this may be explained by exposure to female gonadal hormones 8 . For women, the association between exposure to gonadal hormones and the risk of type 2 diabetes is widely discussed 9‐17 . The findings about the influence of the age of menopause on the risk of type 2 diabetes are controversial 14,15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only Kramer et al . 14 reported that any past usage (no time limit) of hormonal contraceptives (including OCs, injections, patches, cervical rings and intrauterine devices) increased the risk of gestational diabetes compared with no contraception. Given our findings and the review of evidence that OC use may only minimally dysregulate glucose control, 43 an association between OC use and gestational diabetes seems unlikely for those discontinuing before conception.…”
Section: Discussionmentioning
confidence: 99%